Identifying N-linked glycan moiety and motifs in the cysteine-rich domain critical for N-glycosylation and intracellular trafficking of SR-AI and MARCO. Issue 1 (December 2016) - Tsay, Huey-Jen; Huang, Yung-Cheng; Chen, Yi-Jen; Lee, Yun-Hao; Hsu, Shu-Meng; Tsai, Keng-Chang; Yang, Cheng-Ning; Huang, Fong-Lee; Shie, Feng-Shiun; Lee, Lin-Chien; Shiao, Young-Ji
Abstract Background The accumulation of soluble oligomeric amyloid-β peptide (oAβ) proceeding the formation of senile plaques contributes to synaptic and memory deficits in Alzheimer's disease. Our previous studies have indentified scavenger receptor A (SR-A), especially SR-A type I (SR-AI), as prominent scavenger receptors on mediating oAβ clearance by microglia while glycan moiety and scavenger receptor cysteine-rich (SRCR) domain may play the critical role. Macrophage receptor with collagenous structure (MARCO), another member of class A superfamily with a highly conserved SRCR domain, may also play the similar role on oAβ internalization. However, the role of N-glycosylation and SRCR domain of SR-AI and MARCO on oAβ internalization remains unclear. Result We found that oAβ internalization was diminished in the cells expressing SR-AI harboring mutations of dual N-glycosylation sites (i.e. N120Q-N143Q and N143Q-N184Q) while they were normally surface targeted. Normal oAβ internalization was observed in 10 SR-AI-SRCR and 4 MARCO-SRCR surface targeted mutants. Alternatively, the SRCR mutants at β-sheet and α-helix and on disulfide bone formation obstructed receptor's N-glycosylation and surface targeting. Conclusion Our study reveals that N-glycan moiety is more critical than SRCR domain for SR-A-mediated oAβ internalization.